2018
DOI: 10.1089/ten.tec.2018.0040
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Newborn Porcine Models for Evaluation of Tissue-Engineered Small Intestine

Abstract: Short bowel syndrome (SBS) is a major cause of morbidity and mortality in the pediatric population, for which treatment options are limited. To develop novel approaches for the treatment of SBS, we now focus on the development of a tissue-engineered intestine (also known as an "artificial intestine"), in which intestinal stem cells are cultured onto an absorbable bioscaffold, followed by implantation into the host. To enhance the translational potential of these preclinical studies, we have developed three cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Their bioengineered bowel made of the tubular chitosan sheet was confirmed to have vascularization and normal cell phenotype and function after implantation in the small intestine of rats. Moreover, to obtain scaffolds with crypt‐villus architecture, Ladd et al () created a template array of 500 μm deep and ordered holes on a polymethyl‐methacrylate template. They poured either poly(ethylene‐co‐vinyl acetate) or poly(glycerol sebacate) onto the template to cast the crypt‐villus structure on the surface of scaffolds.…”
Section: Biomaterials For Intestinal Organoid Culturementioning
confidence: 99%
“…Their bioengineered bowel made of the tubular chitosan sheet was confirmed to have vascularization and normal cell phenotype and function after implantation in the small intestine of rats. Moreover, to obtain scaffolds with crypt‐villus architecture, Ladd et al () created a template array of 500 μm deep and ordered holes on a polymethyl‐methacrylate template. They poured either poly(ethylene‐co‐vinyl acetate) or poly(glycerol sebacate) onto the template to cast the crypt‐villus structure on the surface of scaffolds.…”
Section: Biomaterials For Intestinal Organoid Culturementioning
confidence: 99%
“…The liquid can be derived from a variety of means, including the melting and solidification of a material ( Im et al, 2019 ), the solubilization of a material in a solvent and subsequent evaporation of the solvent ( Mooney et al, 1995 ; Opitz et al, 2004 ; Nieponice et al, 2008 ; Ma et al, 2010 ; Zakhem et al, 2012 ), or the cross-linking ( Matsuda, 2004 ; Guo et al, 2017 ) or gelation of a material into a solid or semi-solid structure, such as a hydrogel ( Wang et al, 2014 ; Strobel et al, 2018b ). Casting is also applicable within the context of more complex molding techniques, such as vacuum-assisted tube formation ( Singh et al, 2017 ), and for the formation of more complex structures ( Ladd et al, 2018 ). As may be expected, the chosen material will dictate the mechanism.…”
Section: Methods For Fabricating Tubular Scaffoldsmentioning
confidence: 99%
“…The resultant mesh of nanofibers can be removed from the mandrel, producing a mesh-tube (Rocco et al, 2014), with examples producing contiguous tubular structures that are compatible with cell-seeding (Figure 4). In many cases these meshes are combined with secondary electrospinning, deposition, or casting techniques to change Seliktar et al, 2003;Matsuda, 2004;Opitz et al, 2004;Swartz et al, 2005;Liu et al, 2007;Nieponice et al, 2008;Ma et al, 2010;Wang et al, 2014;Guo et al, 2017;Atchison et al, 2017;Strobel et al, 2018b;Im et al, 2019Intestine Yu et al, 2012Zakhem et al, 2012;Chen et al, 2015;Zhou et al, 2018;Ladd et al, 2018Ladd et al, , 2019Roh et al, 2019Trachea Naito et al, 2011 • High degree of control over scaffold properties (porosity, mechanics, etc. ) • Easily applied for tube formation • Directly compatible with proteins…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…91 Of note, some cases demonstrated that surgical complications such as wound infections and hernia would cause the treatment failure and even death. In an updated study, Ladd et al 92 compared the effects of intestinal organoid anastomosis using three surgical types and concluded that a single operation with a defunctionalized loop of small intestine may be an optimal approach. Undoubtedly, such efforts are important for clinical translation of intestinal organoids, and more work is needed for establishing standardized surgical methods.…”
Section: Challenges Of Gut Bioengineering For Clinical Translationmentioning
confidence: 99%